Reducing weed impacts and yield losses by application of herbicides in summer-grown maize - Bogale Ayana (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
A field trial was conducted at Holeta Agricultural Research Station and Medegudina, Central Ethiopia, during the summer season of 2021 to study the effects of different weed control methods against annual grasses and broadleaf weeds in summer planted Maize. The experiment included five treatments; COYOTE 440 SE 3L ha-1, Primagramgold 660 SC 3L ha-1, twice hand weeding, weed-free and weedy check. Major weeds in the fields were Polygonum nepalense, Raphanus raphanistrum, Guizotia scabra, Galinsoga pulviflora, Corrigiola capensis, Caylusea abyssinica, Plantago lanceoleta, Spergula arvensis, Medicago polymorpha, and Phalaris paradoxa. The result signified that the most dominant weed species was Polygonum nepalense with a relative density of 18.28 %. Statistically non-significant results due to all treatments being recorded on ear per plant and 1000 kernel weights at both locations. The results showed that the most effective treatment with higher weed control efficacy (100%) and reduced weed dry weight (0.00 kg/ha) was weed-free. The application of COYOTE 440 SE produced maximum stand count (90 m2), Grain yield (4266 kg/ha), and minimum yield loss (1.49%) while statistically non-significant results were produced in cob per plant and thousand kernel weights. Hence, the study concludes that COYOTE 440 SE 3L ha-1 and weed-free could be more effective as compared to all other treatments without compromising on maize grain yield loss due to weeds.